Efficient osteogenic differentiation of the dental pulp stem cells on β‐glycerophosphate loaded polycaprolactone/polyethylene oxide blend nanofibers. Issue 8 (11th January 2019) - Hosseini, Fatemeh Sadat; Enderami, Seyedeh Elnaz; Hadian, Ali; Abazari, Mohammad Foad; Ardeshirylajimi, Abdolreza; Saburi, Ehsan; Soleimanifar, Fatemeh; Nazemisalman, Bahareh
Abstract: Hard tissue lesion treatment in oral and maxillofacial has been challenging because of tissue complexities. This study aimed to investigate novel biopolymeric construct effects on the osteogenic differentiation potential of the dental pulp stem cells (DPSCs) for introducing a cell copolymer bioimplant. A blended polycaprolactone (PCL)‐polyethylene oxide (PEO) was fabricated using electrospinning, simultaneously filled by β‐glycerophosphate (β‐GP). After that biocompatibility and release kinetics of the PCL‐PEO+β‐GP was evaluated and compared with PCL‐PEO and then the osteogenic differentiation potential of the DPSCs was examined while being cultured on the scaffolds and compared with those cultured on the culture plate. The results demonstrated that scaffolds have not any cytotoxicity and β‐GP can release in a long‐term manner. Alkaline phosphatase activity and calcium content were significantly increased in DPSCs while being cultured on the PCL‐PEO+β‐GP compared with the other groups. Runt‐related transcription factor 2, collagen type‐I, osteonectin, and osteocalcin (OSC) genes expression was upregulated in DPSCs cultured on the PCL‐PEO+β‐GP and was significantly higher than those cultured on the PCL‐PEO. Immunocytochemistry result also confirmed the positive effects of PCL‐PEO+β‐GP on the osteogenic differentiation of the DPSCs by presenting a higher OSC protein expression. According to the results, incorporation of the β‐GP in PCL‐PEO makes a better construct for osteogenic induction into the stem cells and it could be also considered as a great promising candidate for bone, oral, and maxillofacial tissue engineering applications. Abstract : A blended polycaprolactone (PCL)‐polyethylene oxide (PEO) was fabricated using electrospinning, simultaneously filled by β‐glycerophosphate (β‐GP). After biocompatibility and release kinetics characterization of the PCL‐PEO and PCL‐PEO+β‐GP, then osteogenic differentiation potential of the dental pulp stem cells was evaluated while being cultured on scaffolds. Results demonstrated that incorporating of the β‐GP in PCL‐PEO made it a better construct for osteogenic induction and it could be considered as a great promising potential for use in bone, oral, and maxillofacial tissue engineering.